Impact of community forestry on women's workload and the use of chemical fertilizer (Journal of Forest and Livelihood, 2024)
A case study of Gaukhureshwor Community Forest User Group (FUG) of Kavrepalanchwok district shows that community-managed forests over the past several years has increased the supply of forest products particularly leaf litter. An increased supply of forest products has significantly reduced the workload of women in the area. In addition farmers have significantly reduced the use of chemical fertilizer in their farmland. These two positive effects of community forestry can have a favorable impact on the sustainable rural livelihoods.